A developmental basis for the anatomical diversity of dermis in homeostasis and wound repair. Issue 3 (4th December 2020) - Usansky, Ivy; Jaworska, Patrycja; Asti, Ludovica; Kenny, Fiona N; Hobbs, Carl; Sofra, Vasiliki; Song, Hanfei; Logan, Malcolm; Graham, Anthony; Shaw, Tanya J
Abstract: The dermis has disparate embryonic origins; abdominal dermis develops from lateral plate mesoderm, dorsal dermis from paraxial mesoderm and facial dermis from neural crest. However, the cell and molecular differences and their functional implications have not been described. We hypothesise that the embryonic origin of the dermis underpins regional characteristics of skin, including its response to wounding. We have compared abdomen, back and cheek, three anatomical sites representing the distinct embryonic tissues from which the dermis can arise, during homeostasis and wound repair using RNA sequencing, histology and fibroblast cultures. Our transcriptional analyses demonstrate differences between body sites that reflect their diverse origins. Moreover, we report histological and transcriptional variations during a wound response, including site differences in ECM composition, cell migration and proliferation, and re‐enactment of distinct developmental programmes. These findings reveal profound regional variation in the mechanisms of tissue repair. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.